2021
DOI: 10.1021/acsomega.1c05206
|View full text |Cite
|
Sign up to set email alerts
|

Trace Amount of NiP2 Cooperative CoMoP Nanosheets Inducing Efficient Hydrogen Evolution

Abstract: As a very attractive clean energy, hydrogen has a high energy density and great potential to achieve zero pollution emission. Therefore, the preparation of hydrogen evolution electrocatalysts with excellent performance is an urgent task to ameliorate the global energy shortage and environmental pollution. Here, a trace amount of NiP 2 coupled with CoMoP nanosheets (NCMP) was synthesized by the one-step hydrothermal method and low-temperature phosphidation. Studies have found that although the dosage of NiP 2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The overpotentials required to produce a current density of 10 mA cm –2 of 3Mn–NiP were 164 and 77 mV at acidic and alkaline solutions, respectively. Wang et al 123 demonstrated a one-step hydrothermal method for synthesizing NiP 2 with CoMoP nanosheets (NCMP) under low-temperature phosphidation conditions. In the synthesized electrocatalyst, the synergistic effect of two different components, NiP 2 and CoMoP, is induced.…”
Section: Her Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overpotentials required to produce a current density of 10 mA cm –2 of 3Mn–NiP were 164 and 77 mV at acidic and alkaline solutions, respectively. Wang et al 123 demonstrated a one-step hydrothermal method for synthesizing NiP 2 with CoMoP nanosheets (NCMP) under low-temperature phosphidation conditions. In the synthesized electrocatalyst, the synergistic effect of two different components, NiP 2 and CoMoP, is induced.…”
Section: Her Electrocatalystsmentioning
confidence: 99%
“…(g) Long-term stability of NCMP-2 at a constant overpotential for 10 h in 1 M KOH. Data taken from ref ( 123 ).…”
Section: Her Electrocatalystsmentioning
confidence: 99%
“…Nevertheless, both investigations offer valuable insights into understanding the Co n MoP system and serve as significant references for further research in related domains. Wang et al [17] used a one‐step hydrothermal and low‐temperature phosphatization method to prepare a trace amount of NiP 2 coupled Co‐Mo‐P nanosheets (NCMP), and it was found that although the amount of NiP 2 was very low, its presence effectively improved the hydrogen precipitation reaction (HER) performance of Co‐Mo‐P. The exploration of highly active and stable non‐precious metal electrocatalysts in alkaline media is of great significance for the wide application of HER hydrogenolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[25] According to this theory, the catalysts combining Ni with other transition metals can be designed. [26] Among many candidate materials, NiMo-based catalysts are widely used in the study of HER [27][28][29][30] and OER, [31,32] showing excellent performance. Kotaro et al composited the NiMoN nanosheets supporting on carbon with 75 mV overpotential (10 mA cm À 2 ) for HER [33] and the NiMoO 4 synthesized by Chen et al through hydrothermal method showed excellent OER performance under alkaline environment afforded 10 mA cm À 2 at 340 mV.…”
Section: Introductionmentioning
confidence: 99%
“…According to this theory, the catalysts combining Ni with other transition metals can be designed [26] . Among many candidate materials, NiMo‐based catalysts are widely used in the study of HER [27–30] and OER, [31,32] showing excellent performance. Kotaro et al.…”
Section: Introductionmentioning
confidence: 99%